The Influence of Familial Ethnic Socialization on Self-Esteem among Banyumasan Javanese Adolescents as Mediated by Ethnic Identity - Maulidha, Valendra Inaya Fatra; Thontowi, Haidar Buldan (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Negative stereotypes have often positioned the Banyumasan Javanese community as a marginalized group within the broader Javanese society. This is particularly due to their use of the ngapak dialect, which is often viewed as shameful and lacking prestige. However, this study demonstrates that Banyumasan youth today exhibit relatively high levels of self-esteem. The study involved 453 participants, using a convenience sampling method. The results from a simple mediation analysis showed a significant influence of familial ethnic socialization on the self-esteem of Banyumasan adolescents through the mediation of ethnic identity. These findings suggest that strengthening adolescents’ ethnic identity through their families’ ethnic socialization may enhance their self-esteem. Future research is recommended to focus on populations with lower levels of self-esteem and weaker ethnic identity, as the influence of familial ethnic socialization may be more evident in such groups.